# how do you solve the problem (3x+2) - 2(x+4)=7

### 4 Answers | Add Yours

First start by simplifying the right hand side:

(3x + 2) - 2(x+4)

= 3x + 2 - 2x - 8 (multiply through second part by -2)

= x - 6 (combine like terms)

Now we just have to solve: x - 6 = 7

**x = 13** (add 6 to each side)

Since this includes paranthesis, you have to do the order of operations by PEMDAS

(3x+2) - 2(x+4)=7

(3x+2)-2x-8=7

Now move all the numbers to one side and the variables on another

3x-2x=7+8-2

x=13

( 3x + 2 ) - 2 ( x + 4 ) = 7

First distribute the -2

By distributing your equation will look like

**3x + 2 - 2x - 8 = 7 **Now combine the like terms

By combining the like terms, your equation should look like

**x - 6 = 7 **now add 6 on both sides

By adding , your equation should look like

**x = 13 **which is your answer

`(3x+2) - 2(x+4)=7`

`3x+2-2x-8=7 ` combine like terms

`3x-2x+2-8=7`

x-6=7 now add 6 on both sides

+6 +6

**x=13**